Efektivitas Penggunaan Metode Bermain ( Kartu Huruf dan Gambar ) Untuk Meningkatkan Prestasi Belajar Membaca Siswa Kelas III Madrasah Ibtidaiyah Darussalam Kota Bengkulu - Hartati, Hartati (Yayasan Darusssalam Bengkulu, 2020)
The purpose of this study was to determine the effectiveness of the use of play methods (letter cards and images) to improve reading achievement in third grade students of the Madrasah Ibtidaiyah Darussalam Bengkulu City. This research is a quantitative research, using an experimental method with a correlational approach. The population of this study was all children with learning difficulties of third grade students of Bengkulu City Madrasah Ibtidaiyah Darussalam as many as 11 students. As a sample of this study, the researchers took all of the existing population that is all children having difficulty learning third grade students of Madrasah Ibtidaiyah Darussalam Bengkulu City as many as 11 students. Data collection techniques used were the test method as the main method and the method of interview or interview and observation as the method of his help. While the data analysis technique used is the analysis of the Signed Ranking Test (Wilcoxon Sign Ranks Test). Based on the results of this study it can be concluded that there is a significant difference between students' reading learning achievement before being given treatment and after being given treatment. In other words, the method of playing with media cards letters and images effectively used to improve learning achievement of children who have difficulty learning to read class III Madrasah Ibtidaiyah Darussalam Bengkulu City. This is evidenced by the results of data analysis obtained the calculated Z value of -2.946 with a probability of 0.003 and the probability value of the Z count is smaller than the probability of error that is 0.005 with a significance level of 5%.